The Effect of Yellow and White Lupine Meals on the Growth Performance, Carcass Composition, and Meat Quality of Fleckvieh Finishing Bulls - Bartoň, Luděk; Bureš, Daniel; Lebedová, Nicole; Jančík, Filip; Štolcová, Magdaléna; Consolacion, Jerico; Kokošková, Tersia (Animals, 2025)
The aim of the study was to investigate the incorporation of white (WL) and yellow lupine (YL) seed meal as a replacement for rapeseed meal (RS) in the diets of finishing bulls with respect to growth, serum biochemical parameters, carcass composition and meat quality, including sensory analysis. A total of 30 Fleckvieh bulls (average initial weight 441 kg; SD = 33 kg) were housed under identical conditions and fed ad libitum diets similar in protein and energy contents, but with different protein sources-YL seed meal (70 g/kg DM), WL seed meal (77 g/kg DM), and RS meal (75 g/kg DM)-for an average of 85 days. The RS bulls gained weight more rapidly (p < 0.05) and were more efficient (lower feed to gain ratio; p < 0.001) than the YL animals, with the WL group being intermediary. The slaughter and carcass traits, most blood parameters, and meat quality attributes measured in two different muscles were not affected by diet. The proportions and contents of saturated and monounsaturated fatty acids were higher in YL and WL meat (p < 0.001), whilst polyunsaturated fatty acid proportions were higher in RS meat (p < 0.001). Several meat texture characteristics were slightly more favourable in the YL samples compared to the other treatment groups. In conclusion, WL could be used as a replacement of RS in the diets for finishing bulls. However, further research is needed to examine different varieties and inclusion levels of YL in cattle feeding.
Keywords: lupine seed; carcass traits; fatty acid; cattle; sensory analysis; feed intake; blood biochemistry